On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini) - Faille, Arnaud; Ribera, Ignacio; Fresneda, Javier (Zootaxa, 2016)
Aphaobius haraldi sp. n. from the mesovoid shallow substratum (MSS) of the Austrian Alps is described, illustrated, and compared with the closest species of the genus. The new species belongs to the A. kraussi species group, formerly including five species. It can be readily separated from other species of the genus by the large parameres, with an enlarged apical part, a unique feature among species of Aphaobius. The phylogenetic position of the new species is clarified using mitochondrial and nuclear data of four related species of Aphaobius, plus some representatives of related genera from the same geographic area. The diversification of the group was estimated to be recent, dating from the Pleistocene. New records and molecular data are provided regarding the enigmatic monospecific genus of the Austrian Alps, Lotharia Mandl, 1944, which was found to be sister to the studied species of Aphaobius.